Progress in solid oxide fuel cells (Wiley-Interscience, 2006)
This work provides a collection of current research papers including valuable insights on materials-related aspects of solid-oxide fuel cells current status, processing and fabrication, various electrolytes, anodes, and cathodes, ceramic/metal interconnects, seal materials, mechanical properties, characterization, modeling, fuel reforming, component materials, materials processing, performance, stability, and more.